Gambaran Kesadaran Diri pada Masyarakat di Desa Sukobubuk, Kecamatan Margorejo, Kabupaten Pati Terkait Reboisasi - Sumanto Sumanto (Universitas Maritim AMNI Semarang, 2025)
Community awareness is very diverse in responding to environmental protection through reforestation or greening which is always driven by the current government. The diversity of society gives different colors in responding to the government's invitation. Social society plays a role in various problems that arise in society, although it actually aims to improve the lifestyle of the community itself. On the other hand, there are around 100 Ha of area that need reforestation. This study aims to determine the level of self-awareness of the people of Sukobubuk Village, Margorejo District, Pati Regency regarding the implementation of reforestation. The research method uses the informant equatorial method. This study consists of 7 elements of society as informants. Based on the results of this study, it can be concluded that the self-awareness of the people of Sukobubuk Village, Margorejo District, Pati Regency is on average very good. This awareness arises because it is based on direct experience experienced by the community, namely with the occurrence of floods, landslides and the increasing difficulty of clean water needs during the dry season. This efforts made to build self-awareness include community empowerment through mutually beneficial reciprocal cooperation, including providing free land incentives to farmers on the condition that they care for reforestation plants.